2015
DOI: 10.23937/2378-3672/1410013
|View full text |Cite
|
Sign up to set email alerts
|

Immunobiology of S100A8 and S100A9 Proteins and Their Role in Acute Inflammation and Sepsis

Abstract: Toll-like receptors (TLRs) constitute a protein family of cellular receptors that mediate the recognition of microbial challenges and the subsequent inflammatory response. The role of these receptors in allergic diseases of airways remains unclear. The objective of this study was to evaluate TLR2 and TLR4 expression in the lung in a murine model of bronchial hypersensitivity to Aspergillus fumigatus. Different groups of 5-month-old mice (Balb/c) were housed in cages containing hay bedding that was contaminated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
(30 reference statements)
0
16
1
Order By: Relevance
“…During inflammation, S100A8 and S100A9 are actively released and exert a critical role in modulating the inflammatory response by stimulating leukocyte recruitment and inducing cytokine secretion. S100A8 and S100A9 may play a dual role in inflammation, and their pro-inflammatory activity can switch to anti-inflammatory probably depending on the local microenvironment ( El Gazzar, 2015 ). Our results did not allow us to establish if the increased levels of S100A9 and S100A8 observed in saliva of AD patients were linked to a pro- or anti-inflammatory role; however, they agree with studies performed by other research groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During inflammation, S100A8 and S100A9 are actively released and exert a critical role in modulating the inflammatory response by stimulating leukocyte recruitment and inducing cytokine secretion. S100A8 and S100A9 may play a dual role in inflammation, and their pro-inflammatory activity can switch to anti-inflammatory probably depending on the local microenvironment ( El Gazzar, 2015 ). Our results did not allow us to establish if the increased levels of S100A9 and S100A8 observed in saliva of AD patients were linked to a pro- or anti-inflammatory role; however, they agree with studies performed by other research groups.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidation may represent a switch, whereby the modified proteins display anti-inflammatory functions, such as that demonstrated for S100A8-SNO ( Lim et al, 2008 ); S100A9 and S100A8 are able also to act as ROS/RNS scavengers; in particular, S100A8 is sensitive to oxidative cross-linking and massive oxidation and shows capacity to reduce oxidative damage ( Goyette and Geczy, 2011 ). Changes in the inflammatory microenvironment, PTMs of S100A8 and S100A9, binding with transition metals (Zn 2+ and Ca 2+ ), and S100A8/S100A9 heterodimer formation most likely play an important role in the functional switching of these pleiotropic proteins ( El Gazzar, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…S100A9 translocates into the nucleus to upregulate the transcription of microRNAs miR-21 and miR-181b that fine tune the expansion and the functions of MDSCs. Mice lacking S100A9 have less splenic and bone marrow MDSCs especially during late sepsis and are protected from death (61, 62). In vivo blockade of miR-21 and miR-181 decreases bone marrow MDSCs and improves sepsis survival (63).…”
Section: Mdscs Expansion and Activationmentioning
confidence: 99%
“…A link was found between S100A8 and S100A9 protein expression and sepsis pathophysiology 9 . The study showed that increase in S100A8/A9 protein complex occurred systemically during Escherichia coli -induced abdominal sepsis in mice 10 .…”
mentioning
confidence: 97%
“…Activation of p38 mitogen-activated protein kinases phosphorylates S100A9. Intracellularly, this complex binds to actin resulting in cytoskeletal reorganization and when released extracellularly, it mediates inflammatory mediators 9 .…”
mentioning
confidence: 99%